Effect of Steamed Broccoli Juice (Brassica oleraceae L. var. italica) to the Serum Interleukin 8 Level in Colitis Murine Model - Lukas Mulyono Samuel; Francisca AS; Khie Khiong (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Background: Ulcerative colitis (UC) is a bowel inflammation that happens in the colon and rectum. In UC there is an increased level of inflammatory mediators, one of which is interleukin-8 (IL-8), the main chemoattractant for polymorphonuclear (PMN) inflammatory cells causing inflammation to worsen. Broccoli (Brassica oleraceae L. var. italica) contains sulforaphane which can inhibit nuclear factor kappa B (NF-ĸB), resulting in the decrease of IL-8. This study was performed to identify the effect of steamed broccoli juice to the serum interleukin-8 level in murine model of colitis.Method: This study was a true experimental laboratory study using complete randomized design. Experimental animals being used were 28 murines with Balb/c strain and were divided into 4 intervention groups. Serum IL-8 level was measured by using enzyme-linked immunosorbent assay (ELISA) method. Data analysis was performed using analysis of variance (ANOVA) test, followed by multiple comparisons Tukey honest significant difference (HSD) test (a = 0.05) and p  0.05.Results: The highest mean of IL-8 level was found in the positive control group. This study also showed highly significant difference (p 0.001) of IL-8 level between positive control group and treatment group.Conclusion: Steamed broccoli juice could decrease serum interleukin-8 level in murine model of colitis.